Combining graph neural network with deep reinforcement learning for resource allocation in computing force networks - Han, Xueying; Xie, Mingxi; Yu, Ke; Huang, Xiaohong; Du, Zongpeng; Yao, Huijuan (Frontiers of information technology & electronic engineering, 2024)
Fueled by the explosive growth of ultra-low-latency and real-time applications with specific computing and network performance requirements, the computing force network (CFN) has become a hot research subject. The primary CFN challenge is to leverage network resources and computing resources. Although recent advances in deep reinforcement learning (DRL) have brought significant improvement in network optimization, these methods still suffer from topology changes and fail to generalize for those topologies not seen in training. This paper proposes a graph neural network (GNN) based DRL framework to accommodate network traffic and computing resources jointly and efficiently. By taking advantage of the generalization capability in GNN, the proposed method can operate over variable topologies and obtain higher performance than the other DRL methods.